Muatan Nilai-Nilai Spiritualitas Dalam Menguatkan Karakter Religious Mahasiswa Di Universitas Muhammadiyah Bandung - Amriani, Amriani; Maftuh, Bunyamin; syarief, Encep; Safe'i, Makhmud (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
This study aims to determine the application of spiritual values in strengthening the religious character of students. This study is very important to research considering that religious character is an essential value to create a strong and superior generation of the nation. This study uses qualitative research with a descriptive case study approach. Collecting data using observation, interviews and documentation. The subjects in this study were five students at a private university in Bandung, Indonesia. Data were analyzed through the stages of data reduction, presentation, verification, and conclusions. The results of this study indicate that spiritual values can be used as a strategy to strengthen students' religious character. Thus, the field of education cannot be separated from spiritual values to strengthen the religious character of generations of people who are responsible, independent, moral and have noble character so that they contribute to religion and the state.